2017
DOI: 10.1002/pmic.201700005
|View full text |Cite
|
Sign up to set email alerts
|

Functional dual hydrophilic dendrimer‐modified metal‐organic framework for the selective enrichment of N‐glycopeptides

Abstract: Analysis of protein glycosylation remains a significant challenge due to the low abundance of glycoproteins or N-glycopeptides. Here we have synthesized an amino-functionalized metal-organic framework (MOF) MIL-101(Cr)-NH whose surface is grafted with a hydrophilic dendrimer poly(amidoamine) (PAMAM) for N-glycopeptide enrichment based on the hydrophilic interactions. The selected substrate MOF MIL-101(Cr) owns high surface area which provides nice support for peptide adsorption. In addition, the MOF displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Dendrimers, as a class of regularly branched polymers, possess a well-defined size, a compact shape, and a large number of functional end groups. Dendrimers have also been used for wastewater treatment , and various environmental applications. , The polypropylene nonwoven functionalized with PPI dendrimers showed a great ability to remove textile dyes from the aqueous media …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dendrimers, as a class of regularly branched polymers, possess a well-defined size, a compact shape, and a large number of functional end groups. Dendrimers have also been used for wastewater treatment , and various environmental applications. , The polypropylene nonwoven functionalized with PPI dendrimers showed a great ability to remove textile dyes from the aqueous media …”
Section: Introductionmentioning
confidence: 99%
“…Dendrimers have also been used for wastewater treatment 43,44 and various environmental applications. 45,46 The polypropylene nonwoven functionalized with PPI dendrimers showed a great ability to remove textile dyes from the aqueous media. 22 In this study, we have hypothesized that the magnetic properties of Fe 3 O 4 nanoparticles along with a highly stable nanoporous structure of Zr-based MOF (UiO-66) possessing a high specific surface area could be combined to provide a highly efficient nanoporous magnetic adsorbent for wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the alternative methods are necessary. In this regard, previous studies showed that magnetic‐based sorbents including dendrimers have decreased the time required for the sample preparation considerably since they can be easily separated from the mediums applying a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table S3 (ESI†), the capture performance of the probe is in the top-rank and significantly superior to previously reported composites. 14,17,18,26–32…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table S3 (ESI †), the capture performance of the probe is in the top-rank and significantly superior to previously reported composites. 14,17,18,[26][27][28][29][30][31][32] N-Glycoproteomic profiling of clinical samples Hepatocellular carcinoma (HCC) is one of the most malignant cancers with high morbidity and mortality. The high death rate of HCC is primarily related to the fact that most HCC cannot be diagnosed promptly and accurately.…”
Section: Capture Of N-linked Glycopeptides In Mimic Complex Samplementioning
confidence: 99%